ECONOMIC LIFE IN THE KURDISH COUNTRY IN GREEK BOOKS (480-21 BC) - Ali, Jotyar; Ahmmed, Rebar (Humanities Journal of University of Zakho, 2025)
Classical sources are considered significant for the history of Kurdistan, particularly in the economic aspect, The economy has been a crucial factor in Kurdish life since the first millennium B.C., with the people of Kurdistan engaged in agriculture, industry, and livestock farming. Additionally, Kurdistan’s wealth in natural resources and dense forests contributed to its economic strength. These factors played a key role in the development of trade. Moreover, Kurdistan’s richness was a major reason for numerous external attacks throughout different periods in history.